Elderly School in DKI Jakarta: Promoting Robust Elderly Health by Adopting the Lifelong Learning Concept - Tri Suratmi; Sarah Handayani; Dinni Agustin (Science Tech Group, 2026)
An aging population has occurred in DKI Jakarta Province, as data show the elderly population has exceeded 10% of the total population since 2020. Human aging occurs naturally, leading to declines in organ function and functional capacity. Innovative health promotion efforts are needed to effectively maintain the independence of the elderly and keep them healthy. The